Macroeconomic theory and policy - Zahn, Frank (Englewood Cliffs, N.J., Prentice-Hall, 1975)
The book is organized on the premise that once the basic theoretical and technical materials which make up a macroeconomic model are familiar to students, analysis of macroeconomic problems and consideration of remedial policy alternatives can be undertaken with relative ease.
Includes index
Includes bibliographies.
II 17/01/2019
Loans
Keywords: Macroeconomics; Economic policy